The effects of cortisone acetate on stomach evacuation and the absorption of (125)I-labelled globulins in young rats - Morris, B. (1974)
1. After short exposure (3-5 hr) to I.P. cortisone acetate (5 mg), the reduced transmission of labelled globulin to the circulation in 14-day-old rats is due to the slow release of the oral dose from the stomach. The ability of the small intestine to absorb and transmit globulin to the circulation is comparable in control and experimental animals. 2. About 26 hr after cortisone acetate treatment (5 mg), the greatly reduced absorption of labelled globulin from oral doses administered to rats aged 15 days is due to the combined effects of the slower release of the dose from the stomach and to changes which have occurred in the small intestine. 3. About 50 hr after the administration of 5 mg cortisone acetate the effect on the rate of stomach evacuation is minimal in rats aged 16 days. When labelled globulin is introduced directly into the duodenum of these animals virtually no absorption occurs. 4. The results obtained from the experiments in which labelled globulin was injected into the duodenum support the contention that the proximal half of the small intestine is an important site for macromolecular transport.